Marked Direct Hyperbilirubinemia due to Ceftriaxone in an Adult with Sickle Cell Disease - Daniyeh Khurram; Leonid Shamban; Robert Kornas; Maryann Paul (Case Reports in Gastrointestinal Medicine)
Drugs are a significant cause of liver injury. Drug-induced liver injury (DILI) can cause acute hepatitis, cholestasis, or a mixed pattern. Ceftriaxone is a commonly used antibiotic and has been associated with reversible biliary sludge, pseudolithiasis, and cholestasis. A 32-year-old male with sickle cell disease was admitted to the hospital for acute sickle cell crisis. On the second day of hospitalization, he developed cough and rhonchi with chest X-ray revealing right middle lobe infiltrates. Ceftriaxone and azithromycin were initiated. Subsequently, he developed conjugated hyperbilirubinemia and mild transaminitis. His total bilirubin trended upwards from 3.3 mg/dL on admission to 17 mg/dL. It was predominantly conjugated bilirubin, with preadmission bilirubin levels of 3-4 mg/dL. His transaminases were mildly elevated as well compared to previous levels. Extensive workup for bilirubin elevation was unremarkable. Ceftriaxone was switched to levofloxacin and the hyperbilirubinemia improved. On ambulatory follow-up, his bilirubin remained below 4 mg/dL. Ceftriaxone may be associated with marked direct hyperbilirubinemia particularly in sickle cell patients with chronic liver chemistry abnormalities. In the case of elevated bilirubin with concomitant ceftriaxone use, elimination of the offending agent should be considered.